Effect of dietary soy acid oil on growth performance, nutrient utilization and haemato-biochemical parameters in Ven cobb broiler chicken - DUBEY, MEENU; TIWARI, S P; DONERIA, RAINA (The Indian Journal of Animal Sciences, 2015)
Day-old Ven cobb broiler chicks (360) were randomly allocated to 6 treatment groups with 4 replicates of 15 chicks in each to see the effect of different levels of soy acid oil on growth performance, nutrient utilization and haemato-biochemical parameters of them. The starter (0-14 d), grower (14-28 d) and finisher (28-42 d) diets contained 23, 21.5 and 20% CP and 2,900, 3,025 and 3,100 kcal ME/kg, respectively. Group T1 was control, T2-T6 contained graded level (1, 1.5, 2, 2.5 and 3% of diet, respectively) of soy acid oil (SAO). Body weight and feed intake at 6 week were significantly higher in birds fed diet with 2.5 and 3% SAO. The FCR was significantly better in group T5. The level of SAO in the diet of broiler chickens did not influence the per cent metabolizability of dry matter, however the apparent metabolizable energy value was significantly higher in the birds fed diet with higher level of SAO. Incorporation of SAO did not influence the nitrogen, calcium and phosphorus balance. The inclusion of SAO at different levels did not significantly influence the haemoglobin and PCV values amongst the birds of different groups. The increase in the level of SAO resulted into non significant increase in the activity of ALP and SGPT and serum cholesterol and HDL cholesterol concentration. It is concluded that soy acid oil can be incorporated in the diet of broiler chicken without affecting the performance.